2019
DOI: 10.1002/jbmr.3701
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Dinucleotides Inhibit Osteoclast Differentiation Through STING-Mediated Interferon-β Signaling

Abstract: Cyclic dinucleotides (CDNs), such as cyclic diadenylate monophosphate and cyclic diguanylate monophosphate, are commensal bacteria‐derived second messengers in the gut that modulate bacterial survival, colonization, and biofilm formation. Recently, CDNs have been discovered to have an immunomodulatory activity by inducing the expression of type I interferon (IFN) through STING signaling pathway in macrophages. Because CDNs are possibly absorbed and delivered into the bone marrow, where bone‐resorbing osteoclas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 52 publications
1
33
0
Order By: Relevance
“…This discrepancy may possibly be because of the differential amounts of exogenous TBK1 protein expression by the method employed. Furthermore, another recent study indicated that the cytosolic DNA sensor stimulator of interferon genes and its downstream TBK1–interferon regulatory factor 3 signaling cascade are activated during the inhibition of OC differentiation caused by cyclic dinucleotides 27 . These controversial observations suggest that the regulatory effects of TBK1 on bone remodeling are complicated, and may be signal and context dependent.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy may possibly be because of the differential amounts of exogenous TBK1 protein expression by the method employed. Furthermore, another recent study indicated that the cytosolic DNA sensor stimulator of interferon genes and its downstream TBK1–interferon regulatory factor 3 signaling cascade are activated during the inhibition of OC differentiation caused by cyclic dinucleotides 27 . These controversial observations suggest that the regulatory effects of TBK1 on bone remodeling are complicated, and may be signal and context dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CDNs can also influence bone metabolism. CDNs inhibit RANKL-induced osteoclast differentiation from mouse bone marrow-derived macrophages through STING-dependent signaling pathway [ 18 ]. Authors demonstrated that CDNs potently trigger STING-TBK1-IRF3 cascade and induce the mRNA expression of IFN-β during osteoclast differentiation from macrophages.…”
Section: Microbe-associated Molecular Patternsmentioning
confidence: 99%
“…The recognition of MAMPs by pattern recognition receptors (PRRs) is crucial for inducing host immune responses [ 15 ]. In addition, secretory microbial molecules including short chain fatty acid (SCFA), extracellular vesicle (EV), extracellular polysaccharide, and cyclic dinucleotide (CDN) also modulate bone cells [ 16 , 17 , 18 ]. Therefore, for a clear understanding of the regulation of bone metabolism by bacteria, it is essential to understand the effects of MAMPs and secretory microbial molecules on bone cells and their regulatory mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…[114][115][116] There are two sources of CDNs: the cGAS pathway, which produces the atypical dinucleotide 2ʹ,3ʹ-cGAMP after the detection of cytoplasmic DNA; the other is found in the cytoplasm owing to the presence of pathogens. 112,[117][118][119] Numerous studies found that CDNs have strong antitumor effects and application prospects in the treatment of melanoma, colon cancer, and oral cancer. 39,[120][121][122] However, there are limitations in the use of CDNs as candidate drugs.…”
Section: Agonists Of Stingmentioning
confidence: 99%